2004
DOI: 10.1002/bem.10202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 50 Hz electric field on plasma ACTH, glucose, lactate, and pyruvate levels in stressed rats

Abstract: The effect of extremely low frequency electric field (EF) on stress induced changes of plasma ACTH, glucose, lactate, and pyruvate levels was examined in ovariectomized rats. The rats were exposed to 50 Hz EF (17500 V/m) for 60 min and were restrained for the latter half (30 min) of the EF exposure period. The restraint stress significantly increased the plasma ACTH and glucose levels (P <.05: Student's t test). Restraint induced increase of plasma ACTH and glucose levels tended to be suppressed by exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
41
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 10 publications
9
41
0
1
Order By: Relevance
“…And in accordance to Martí, Armario (1997), repeated stress is associated with the sensitivity of glucose, inducing hyperglycaemia. In accordance with Harakawa et al (2004), EMF of 50 Hz increases ACTH, glucose, lactate, and pyruvate levels in stressed rats, demonstrating that the 50 Hz EMF alters both stress responses and energy metabolism in stressed rats.…”
Section: Effects Of Undernutrition and Emf In The Cortisol Serum Concsupporting
confidence: 67%
“…And in accordance to Martí, Armario (1997), repeated stress is associated with the sensitivity of glucose, inducing hyperglycaemia. In accordance with Harakawa et al (2004), EMF of 50 Hz increases ACTH, glucose, lactate, and pyruvate levels in stressed rats, demonstrating that the 50 Hz EMF alters both stress responses and energy metabolism in stressed rats.…”
Section: Effects Of Undernutrition and Emf In The Cortisol Serum Concsupporting
confidence: 67%
“…1) [6]. The exposure cage was comprised of a cylindrical plastic cage (diameter; 200 mm, height; 200 mm) and two electrodes made of stainless steel (400 × 4 0 0 m m ) w e r e p l a c e d o ve r a n d u n d e r t h e cylindrical cage (Fig.…”
Section: Electric Field Exposure Systemmentioning
confidence: 99%
“…Furthermore, we have reported that exposure of restrained rats to an electric field suppressed increases in plasma ACTH, glucose and lactate levels induced by the restraint stress [6]. Although the biological effects of electric field exposure on reproductive function have not been fully identified yet, it has been reported that exposure of mice to magnetic fields had no adverse effects on fertility and reproduction [7,8].…”
mentioning
confidence: 96%
“…Udincew et al [11] observed an increase of 11-OKS to 94% in serum and by 40% in the hormones excreting organs. In contrast, Harakawa et al [12] and Hedges-Dawson et al [13] noted a decrease of the cortisol hormone; however, this decrease occurred some days after (long-term application in rats), which the authors explained as exhaustion of the pituitary-adrenal system due to the longterm exposure [14,15]. Bonhomme-Faivre et al [16] describe decreased changes in the white cells system (neutropenia) in mice exposed to a magnetic field of 5μT induction resulting in a decrease of cortisol concentration on the 190th day of research.…”
Section: Discussionmentioning
confidence: 88%